Tang Kong Meng V Zainon Bt Md Zain: A Case Decided But Not Resolved - Abdullah, Nor Aini (Journal of Malaysian and Comparative Law, 2019)
Case note on Tang Kong Meng V Zainon Bt Md Zain regarding Article 12(4) of the Federal Constitution.